THE STRATEGIC MIND AND ITS ROLE IN ACHIEVING STRATEGIC SUCCESS AN ANALYTICAL DESCRIPTIVE STUDY IN THE IRAQI MINISTRY OF CONSTRUCTION, HOUSING, MUNICIPALITIES, AND PUBLIC WORKS - Mustafa Sabah Hlehel (Scholar Express Journals, 2022)
The research aims to identify the role played by the strategic mind of managers in achieving the strategic success that the organization seeks to achieve. Research in providing a set of solutions to the problems faced by the research organization and as far as research variables are concerned. The researcher adopted the descriptive analytical approach in the practical aspect, as the questionnaire was adopted as a main tool for data collection, which was prepared based on a number of ready-made standards after adapting them to suit the Iraqi environment, Which was distributed to a sample of (67) individuals who hold administrative positions in the Ministry of Construction, Housing, Municipalities and Works, and after processing and analyzing the data using a set of statistical tools, a set of results was reached that confirmed the validity of the hypothesis on which the research was based, and accordingly the conclusion was reached That the independent variable, the strategic mind, contributes to increasing the levels of the dependent variable through its own dimensions, and accordingly I recommend The researcher must activate the role played by the strategic mind for strategic success by creating all the requirements to activate his role and create the appropriate work environment.
Keywords: Strategic mind; strategic success; Ministry of Construction; Housing